High-Sensitivity C-Reactive Protein Is a Predictor of Coronary Microvascular Dysfunction in Patients with Ischemic Heart Disease - Tong, David C.; Whitbourn, Robert; MacIsaac, Andrew; Wilson, Andrew; Burns, Andrew; Palmer, Sonny; Layland, Jamie (Frontiers in Cardiovascular Medicine, 2018)
Background Inflammation and microvascular dysfunction (MVD) are independently associated with adverse cardiovascular outcomes in patients with ischaemic heart disease. This study aimed to assess the relationship between inflammation, MVD and myocardial injury. Methods Coronary microvascular function was assessed in 74 patients undergoing percutaneous coronary intervention (PCI) using the index of microvascular resistance (IMR) by a pressure-temperature sensor-tipped wire. Serum high-sensitivity C-reactive protein (hsCRP) level was quantified by rate turbidimetry. Severe MVD was defined as IMR>30. Pearson correlation was computed to assess the relationships between hsCRP, troponin and IMR of culprit vessel. Predictors of severe MVD were assessed by regression analysis. Results Acute coronary syndromes (ACS) represented 49% of the total cohort. Study cohort was divided into Low CRP (hsCRP<3mg/L) and High CRP (hsCRP>3mg/L) groups. There was higher representation of smokers (78% vs. 52%), diabetics (39% vs. 18%) and ACS (61% vs. 33%), as well as higher BMI (29.4±4.6 vs. 27.2±4.1) in the High CRP group. Pre-PCI and post-PCI IMR were significantly elevated in the High CRP group compared to the Low CRP group (Pre-PCI IMR: 29.0±13.9 vs. 17.4±11.1, p<0.0001; Post-PCI IMR: 23.0±16.8 vs. 15.5±8.4, p=0.02). Peak troponin levels were significantly raised in the High CRP group (9.96±17.19ug/L vs. 1.17±3.00ug/L, p=0.002). There was a strong positive correlation between hsCRP and pre-PCI IMR (r=0.85, p<0.0001). Pre- and post-PCI IMR levels were correlated with peak troponin level (r=0.45, p<0.0001; r=0.33, p=0.005 respectively). Predictors of severe MVD include male gender (OR3.0), diabetes (OR3.7), smoking history (OR4.0), ACS presentation (OR8.5) and hsCRP>3mg/L (OR5.6). Conclusion HsCRP is a significant predictor of microvascular dysfunction whilst MVD is associated with myocardial injury, supporting the central role of inflammation and MVD in the pathophysiology and complications of coronary artery disease.